Bogdanich, Walt y Forsythe, Michael (2023). La Consultora. Cómo McKinsey dirige el mundo. Ediciones Península, 528 páginas. - Franco Bass, Ornella (Cuadernos de Relaciones Laborales, 2025)
There is a popular saying: ‘what is little talked about matters a lot’. This is the idea the authors of the book that will be the subject of this review: La Consultora. The Consultant. How McKinsey runs the world (2023).